Understanding sustainable diets: a descriptive analysis of the determinants and processes that influence diets and their impact on health, food security, and environmental sustainability - Johnston, J.L.; Fanzo, J.C.; Cogill, Bruce (Elsevier, 2014)
The confluence of population, economic development, and environmental pressures resulting from increased globalization and industrialization reveal an increasingly resource-constrained world in which predictions point to the need to do more with less and in a “better” way. The concept of sustainable diets presents an opportunity to successfully advance commitments to sustainable development and the elimination of poverty, food and nutrition insecurity, and poor health outcomes. This study examines the determinants of sustainable diets, offers a descriptive analysis of these areas, and presents a causal model and framework from which to build. The major determinants of sustainable diets fall into 5 categories: 1) agriculture, 2) health, 3) sociocultural, 4) environmental, and 5) socioeconomic. When factors or processes are changed in 1 determinant category, such changes affect other determinant categories and, in turn, the level of “sustainability” of a diet. The complex web of determinants of sustainable diets makes it challenging for policymakers to understand the benefits and considerations for promoting, processing, and consuming such diets. To advance this work, better measurements and indicators must be developed to assess the impact of the various determinants on the sustainability of a diet and the tradeoffs associated with any recommendations aimed at increasing the sustainability of our food system.